Pengaruh Upah, Insentif Dan Jaminan Sosial Terhadap Semangat Kerja Karyawan PT Aquafarm Nusantara Klaten - Novitasari, Dwi Rahmani, Nur Achmad, SE., M.Si (2016)
The purpose of this study was to analyze the effect of wages on employee morale, the effect of incentives on employee morale, analyze the influence of social security on employee morale, and analyzed between wages, incentives and social security which has the most dominant influence on employee morale PT Aquafarm Nusantara Klaten. Research method used quantitative. The primary data of questionnaires distributed directly to employees PT Aquafarm Nusantara Klaten. Samples were taken by simple random sampling are 57 respondents. The data analysis technique uses multiple linear regression analysis. Based on t test results showed that labor costs have a significant influence on employee morale significance value 0.013 <0.05; incentive variables have a significant influence on motivation employee with significant value 0.039 <0.05; social security variables have a significant effect on employee morale with significant value 0.012 <0.05. Variable pay, incentives and social security simultaneously affects the employee morale with a significance value of 0.000 <0.05. The coefficient of determination (R2) note that the adjusted R-square (R2) of 0.361, meaning variation employee morale variable changes can be explained by the variable salary, incentive and social security amounted to 36.1%. While the rest of 63.9% is explained by other variables outside the model.